Improvement of non-electrical engineering student knowledge content and motivation to learnt electronic circuit and system through implementation of hands – on learning - Zaharah Johari,; Azmahani Abd. Aziz,; M. Fairus M. Yusoff,; N. Effiyana Ghazali,; Fatin Aliah Phang, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Electronic circuit and system (ECS) course introduces students to understand the circuit and system operation as well as using tool and technique to solve engineering problem related to circuitry. This course is compulsory offered for both electrical and non – electrical engineering students. The non – electrical engineering student will find this course challenging and difficult to understand especially when it involves circuit design and analysis. Therefore, transforming the learning environment from traditional to innovative approach could help in the enhancement of student learning. Therefore, this paper is presented to assess student reflection after the implementation of hands – on learning towards improvement of content of knowledge and motivation in learning about active filter in ECS course. Students are required to design an active filter using the specification given, verified using simulation tool and doing the actual testing in laboratory. A qualitative study is conducted via survey questionnaire and the student reflections were analyzed using thematic analysis. Results shows an improvement in student content of knowledge and motivation to learnt after the implementation of the hands – on learning. The outcome shows in this study suggest the necessity of including the hands – on learning to maximize student engagement for students as well as achieving the course learning outcome.